MANAJEMEN MUTU GURU PONDOK PESANTREN - Mubarok, Ruma (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
Islamic boarding schools in Indonesia as an educational institution of its existence is enough very old. Along the way, many changes occur, both positive and negative. But the development of the boarding school in the archipelago as the oldest educational institution does not have a significant correlation with the strength or menejemennya progress. Boarding schools have ups and downs, from the colonial period, independence, until the time of the current reform. Kyai as a helm, multifunctional duties, as a teacher, preacher, and managers. As a manager it must improve the quality mutu.Tuntutan better than any cleric become a requirement for boarding institutions. Quality in the sense of the word, they can work with professionals, in accordance with the functions and responsibilities. So also for the leadership of the boarding school can work in a professional manner to meet the needs of the professionalism of teachers, good service, education, health, facilities, and no less important is the economic aspect or the necessities of life of current and future.